Using facebook ads as a recruitment strategy for web surveys on drugs: Experience from the European web survey on drugs - Jerkoviç, D; Lotar Rihtarić, M; Van Laar, M; Horvat, T; Udrisard, R; Matias, J (Adiktologie, 2019)
BACKGROUND: General population surveys present a useful tool for getting information on drug use prevalence, but they often fail to reach a sufficient number of users, which is required to get detailed information on use patterns or other characteristics. Web surveys, especially when they use social networking sites, might present a complementary mechanism for getting a better picture of drug use by reaching hard-to-reach populations. AIM: The main objective of this study was to examine Facebook advertisements as a recruitment strategy in the “European Web Survey on Drugs: patterns of use”, a project organized by the European Monitoring Centre for Drugs and Drug Addiction. METHODS:Recruitment campaigns invited adults aged 18+ years who had consumed at least one drug (cannabis, MDMA/ecstasy, amphetamines, or cocaine) in the past 12 months to complete an online survey. The advertisements were created in Facebook’s Advertisement program and were used in Croatia, Switzerland, and the Netherlands. RESULTS: Among the eligible participants recruited via Facebook (N=5256), 68.1% were from Croatia, 24.4% from Switzerland, and 7.5% from the Netherlands. The Croatian and Swiss participants were younger and more likely to be males compared to the Dutch participants. Chi-square tests showed that there were significant differences in the frequency of drug use between the samples from the different countries for almost all drugs. CONCLUSION:The Facebook recruitment strategy was successful in reaching young adults, as well as recreational drug users, although the costs, campaign duration, available budget, and content of the ad images differed among the countries.